Water footprint profile of crop-based vegetable oils and waste cooking oil: Comparing two water scarcity footprint methods. (10th September 2018) - Caldeira, Carla; Quinteiro, Paula; Castanheira, Erica; Boulay, Anne-Marie; Dias, Ana C.; Arroja, Luís; Freire, Fausto
Abstract: This paper compares the water footprint profiles of four feedstocks used for biodiesel production: palm, soya, rapeseed and waste cooking oil (WCO). The profiles include: (a) a water scarcity footprint related to freshwater consumption impacts and (b) a water quality degradation footprint related to freshwater degradation impacts. The water scarcity footprint was assessed using two impact assessment methods: one based on water stress indices (WSIs) and the other on the available water remaining (AWARE) indicator. The water degradation footprint was assessed considering the environmental mechanisms covered by the impact categories of eutrophication, aquatic acidification, human toxicity and freshwater ecotoxicity. The water scarcity profiles ranged from 0.002 to 2.11 world m 3 eq kg −1 oil (WSI method) and from 0.008 to 133.57 world m 3 eq kg −1 oil (AWARE method). Both methods showed that the cultivation stage assumes the primary role in the water scarcity footprint results and identified the same systems with higher water scarcity footprints. However, for the oil systems with closer results, the rank order given by each method is different due to the characterization factors of each method. Nevertheless, the results obtained with the AWARE method give more comprehensive water scarcity footprint results than those obtained when applying WSIs because AWARE considers the aquatic ecosystem water demand. The water degradation footprint of virgin oils is mainly caused by fertilizers and pesticides used in cultivation. WCO systems present lower impacts for all impact categories with the exception of human toxicity-cancer. The choice of locations with lower water scarcity to produce oil crops can be a determinant in the calculation of lower impacts. Moreover, optimizing fertilization schemes or choosing climatic conditions that require less fertilizers, pesticides and water consumption can reduce the impacts of the water footprint profile of vegetable oils. Highlights: Comparative water footprint (WF) profile of 4 biodiesel feedstocks. Impacts due to freshwater consumption and degradation are assessed. Two impact LCA-based methods were used to assess water scarcity footprint. Cultivation stage contributes the most to the water scarcity footprint. Water quality degradation footprint is mainly caused by fertilizers and pesticides.